1975
DOI: 10.1063/1.1134256
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity piezoelectric accelerometer

Abstract: A high-sensitivity piezoelectric accelerometer has been developed to monitor and characterize low-level vibration spectra in large structures. The theory of accelerometer design is traced and applied to a specific problem to develop a set of design criteria. The construction and calibration of the accelerometer is described. The accelerometer has a sensitivity of 2.82 V/g (9.0 dB re 1 V/g) at frequencies to 1 kHz. The use of the accelerometer in conjunction with a real-time spectrum analyzer to identify vibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…However, practically, the small area of PMN-28PT single crystal was not strongly affixed to the relatively large volume (1000 mm 3 ) and heavy (17.8 g) seismic mass (i.e., the area ratio between the piezoelectric single crystal and the mass was 1:16). The typical compression acceleration sensor manufacturing method, in which a tie bolt is used to bond the mass and piezoelectric elements together through a center hole, is not suitable for use with small piezoelectric component [20,21]. This problem was overcome by using an elastic body support layer with a very low elastic modulus around the piezoelectric component.…”
Section: Sensor Fabrication and Experiments Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, practically, the small area of PMN-28PT single crystal was not strongly affixed to the relatively large volume (1000 mm 3 ) and heavy (17.8 g) seismic mass (i.e., the area ratio between the piezoelectric single crystal and the mass was 1:16). The typical compression acceleration sensor manufacturing method, in which a tie bolt is used to bond the mass and piezoelectric elements together through a center hole, is not suitable for use with small piezoelectric component [20,21]. This problem was overcome by using an elastic body support layer with a very low elastic modulus around the piezoelectric component.…”
Section: Sensor Fabrication and Experiments Resultsmentioning
confidence: 99%
“…On the other hand, there has been limited investigation of vector sensors, especially utilizing the compressive-type accelerometer. Compressive-mode vector sensors are simple in design, and can be easily used in various applications for mechanical and structural monitoring [20,21]. If the vector sensors developed here are aligned with the X, Y, and Z axes inside an omnidirectional hydrophone, they could be used to measure the directivity of an acoustic source for underwater sensor nodes.…”
Section: Introductionmentioning
confidence: 99%
“…The current accelerometers can be classified two types by their adopted sensors. The first type is the accelerometers based on electrical sensors, such as strain gauge [3], [4], piezoelectric sensor [5]- [8] and capacitive sensor [9]- [11]. Strain gauge accelerometers usually have high stability, low cost and a bandwidth of 100 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the accelerometer is 9 mV/g, the linearity is 0.0205, and the hysteresis error is 0.0033. Zou et al [ 4 ], Nishshanka et al [ 5 ], and Tims et al [ 6 ] have also made progress in this field and the detailed data is shown in Table 1 . From Table 1 , we can see that the PZT accelerometers have a wide bandwidth.…”
Section: Introductionmentioning
confidence: 99%